Vom Überleben zum Erleben. Der Weg durch die Wüste - Dangl, Oskar (Protokolle zur Bibel, 1998)
The following conribution inquires the relationship between landscape, religion and personality. First of all a sociological diagnosis will be given. This diagnosis represents the background of the biblical considerations of the problem in question. All this fits to the frame of the so-called pedagogics of experience.